Die Geschichtsauffassung von Alexander von Bronikowski. Zur Geschichte Polens und ihrer fiktionalen Komplementarität - Kałążny, Jerzy (Studia Germanica Posnaniensia, 2018)
The article is an attempt at presentation of Aleksander Bronikowski - author of many historical novels, popular in Poland and in Germany - as a historian who used results of his own research of sources in the creation of literary fiction. The fundamental element of his artistic programme, formulated in the preface to his first historical novel “Hipolit Boratyński” (1825) and realized consistently in subsequent novels devoted to the history of Poland was historical revisionism. In contradistinction to Walter Scott this novelist places in the central point of action not a fictional hero but historical events. "History of Poland", published in 1827, is an outline of the history of the Polish state divided in to five periods since the legendary beginnings until the third partition. To each of these periods may be ascribed the relevant novels on Polish subjects in which Bronikowski gave a novelized and expanded pictures of the presented epoch. Analysis of the list of sources and studies which he used makes it possible to say that he had an excellent knowledge of the achievements of German historiography of those times - Polish, German and French. Interpretation of the fall of Poland, according to the ideas of Enlightenment, as a result of unavoidable ageing of the nation and of structures which it created was criticized by J. Lelewel - the founder and leader of Polish historiography. It is surely for this reason that “The History of Poland” has not been translated into Polish. An open question remains what was the influence of this work and of historical novels, which were like as if a supplement and development, on Polish national awareness of Poles in the years immediately before the outbreak of the November Uprising.